Evaluation of efficacy of oral calcium phosphate as an adjunct to standard-of-care regular phototherapy in cases of neonatal jaundice: a hospital-based double-blind, randomised, placebo-controlled trial - Pradeep Kumar; Arnab Ghorui; Chandra Mohan Kumar; Bhabesh Kant Chowdhry; Pramod Kumar Manjhi (BMJ Publishing Group, 2024)
Objective Neonatal jaundice is the most common cause of neonatal morbidity and rehospitalisation in the first week of life, affecting approximately 60% of term and 80% of preterm neonates, with 10% requiring phototherapy to prevent bilirubin-induced neurological dysfunction. Enterohepatic circulation contributes 10%-20% of the body's bilirubin load, and oral calcium-phosphate can inhibit this process by binding to unconjugated bilirubin and acting as a bilirubin-trapping agent in the gut. This study aimed to evaluate the efficacy of oral calcium phosphate as an adjunct to phototherapy in reducing phototherapy duration, improving bilirubin decline rate and lowering rebound hyperbilirubinaemia incidence.Methods This double-blind, placebo-controlled randomised controlled trial with a 1:1 allocation ratio was conducted in the neonatal intensive care unit of a tertiary care hospital in Eastern India. The investigator and the analyst were blinded to the treatment assignments. Eligible neonates with neonatal jaundice requiring phototherapy as per the 'American Academy of Pediatrics or 'National Institute for Health and Care Excellence' guidelines were enrolled and randomly assigned to receive either oral calcium phosphate or placebo.Results The total duration of phototherapy was significantly lower in the intervention group compared with placebo (18.8±5.63 hours vs 24.3±4.50 hours; mean difference=−5.55 (95% CI −7.82 to −3.28), p<0.001). The rate of fall of bilirubin (mg/dL/hour) was also significantly higher in the intervention group (0.186±0.0137 vs 0.116±0.0088; mean difference=0.0693 (95% CI 0.0642 to 0.0745), p<0.001). The intervention group showed a trend towards a decrease in the incidence of rebound hyperbilirubinaemia, with a relative risk of 0.30 ((95% CI 0.0891 to 1.01), p=0.066).Conclusion The use of oral calcium phosphate results in a statistically significant reduction in phototherapy hours, an improvement in the rate of bilirubin decline and a decrease in rebound hyperbilirubinaemia incidence. This allows for shorter hospital stays and reduces the need for rehospitalisation, resulting in less mother-baby dyad separation, lower hospital resource consumption and reduced financial burden on parents.Trial registration number Clinical-trials-registry-India, Ref No.CTRI/2022/03/041203, dated 21 March 2022https://ctri.nic.in/Clinicaltrials/showallp.php?mid1=57944&EncHid=&userName=Phototherapy.